PENGEMBANGAN BAHAN AJAR BAHASA SASAK BERBASIS HIGH ORDER THINGKING SKILLS - Taufiqqurrahman Taufiqqurrahman; Mohammad Efendi; Sulton Sulton (Pascasarjana Universitas Negeri Malang, 2017)
The research objective is to produce and test the feasibility of textbooks based Sasak language thingking high order skills for junior high school students. The model used is a model development Dick, Carey & Carey until the ninth stage. The product development is validated by subject matter experts with the level of validity 73%, media expert with a degree of validity of 84%, a learning design with a level of validity 90.4%, individual testing with a level of validity to 68%, small group trial with a level of validity 82% and test field trials with a validity rate of 89% with a very worthy qualification does not need revision. Tujuan penelitian adalah untuk menghasilkan dan menguji kelayakan buku bahan ajar bahasa Sasak berbasis High Order Thingking Skills untuk siswa SMP. Model pengembangan yang digunakan adalah model Dick, Carey & Carey sampai pada tahapan yang kesembilan. Pengembangan produk ini divalidasi oleh ahli materi dengan tingkat kevalidan 73%, ahli media dengan tingkat kevalidan 84%, ahli desain pembelajaran dengan tingkat kevalidan 90.4%, uji coba perorangan dengan tingkat kevalidan 68%, uji coba kelompok kecil dengan tingkat kevalidan 82% dan uji coba lapangan dengan tingkat kevalidan 89% dengan kualifikasi sangat layak tidak perlu revisi.